The Influence of Pruning and Differences of Harvest Times Toward Taro Production (Xanthosoma sagittifolium) - Nugraha Ramadhan; Zulfadly Syarief; Indra Dwipa (Warmadewa University Press, 2018)
This research was conducted in Batusangkar, West Sumatera using factorial research in the form of randomized block design (RBD). The species of Taro that used as the experimental material was Taro type in the age of 4 months. The purpose of this research is (1) to know the interaction between leaves pruning and difference of harvest times to the growth and production of Taro, (2) to know the best leaves pruning for growth and production of Taro (3) to know the best harvest times in order to get the best Taro production. The treatments of leave pruning in this study consisted of; without pruning, pruning by leaving 4 leaves, and pruning by leaving 6 leaves. On the other hand, the harvest times treatment is on 6 months, 7 months, and 8 months. The results showed that the interaction between leave pruning and harvesting times affected taros’ tuber diameter. On the form of tuber wet weight and length, there was no a significant effect due to the treatment provided, yet the pruning by leaving 6 leaves effected to increase the number of tubers and the productivity of Taro. While the best harvest times to increase the productivity of Taro is at the age of 7 and 8 months.